2021
DOI: 10.2174/1874350102114010001
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Social Identity Model of Collective Action in the Context of Vietnam

Abstract: Introduction: Although collective action relating to land and environmental disputes in Vietnam has been increasing over the past decades, there is little research from the perspective of social psychology on this topic. Objective: This study was conducted to examine the applicability of the social identity model of collective action [SIMCA] in the context of Vietnam. Specifically, we assessed the predictive powers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Anger is one of the most heavily researched approach-oriented emotions that involved in protest behavior. According to the Social Identity Model of Collective Action (SIMCA; van Zomeren, Postmes, et al, 2008), perceived injustice, through the experience of relative deprivation, invokes feelings of anger among members of disadvantaged groups, and this group-based anger in turn predicts willingness to protest and participate in collective action (Nguyen et al, 2021;Shepherd & Evans, 2020).…”
Section: Hope For Better Societiesmentioning
confidence: 99%
“…Anger is one of the most heavily researched approach-oriented emotions that involved in protest behavior. According to the Social Identity Model of Collective Action (SIMCA; van Zomeren, Postmes, et al, 2008), perceived injustice, through the experience of relative deprivation, invokes feelings of anger among members of disadvantaged groups, and this group-based anger in turn predicts willingness to protest and participate in collective action (Nguyen et al, 2021;Shepherd & Evans, 2020).…”
Section: Hope For Better Societiesmentioning
confidence: 99%
“…While some studies found it to explain environmental collective action (Bamberg et al, 2015, Study 1;Furlong & Vignoles, 2021;Haugestad et al, 2021;Keshavarzi et al, 2021), an increasing number of studies showed that collective efficacy does not predict collective action when other factors are considered Nguyen et al, 2021;van Zomeren et al, 2019;Wallis & Loy, 2021;but see van Zomeren et al, 2010). Similarly, we find studies showing that affective injustice predicts environmental collective action (Keshavarzi et al, 2021;Nguyen et al, 2021;van Zomeren et al, 2019;Wallis & Loy, 2021), and does not when other factors are accounted for Furlong & Vignoles, 2021).…”
Section: Predictors Of Collective Actionmentioning
confidence: 99%
“…Fourth, since conducting Study 1, more factors have been proposed to extend the original SIMCA that we sought to include. Agostini and van Zomeren (2021) published the dual chamber model comprising moral convictions (i.e., issue-specific attitudes that are based on core values, see alsoNguyen et al, 2021). Moreover, research suggests that injunctive norms (what other people think is good) and descriptive norms (what other people do) are important predictors of collective action that are oftentimes neglected…”
mentioning
confidence: 99%
“…Research testing the explanatory and predictive power of the Social Identity Model of Collective Action (SIMCA: Van Zomeren et al, 2008) has confirmed the central roles of collective identity, efficacy, negative emotions, and moral conviction in motivating non-activists to participate. While some research in Asian countries has found that SIMCA variables could be moderated by cultural factors, such as collectivism (Fukuzawa & Inamasu, 2020), other studies have found no evidence of cultural differences (e.g., Nguyen et al, 2021). However, this framework remains largely untested amongst other groups who may participate or observe collective action (e.g., journalists) and cultural contexts (van Zomeren, 2019).…”
mentioning
confidence: 99%